Radiological Evaluation of Appendicitis and Its Impact on Negative Appendectomy Rates - Israr, Shumaila; Jehan, Badar; Bano, Farhat; Tariq, Asmaa; Tahseen, Hina; Abdullah, Zainab (Journal of Neonatal Surgery, 2025)
Background: Acute appendicitis is one of the most common causes of acute abdomen requiring emergency surgery. Reliance on clinical assessment alone is associated with a significant rate of negative appendectomy, leading to avoidable morbidity and increased healthcare costs. Radiological imaging has been increasingly incorporated into diagnostic pathways to improve accuracy and optimize surgical decision-making. Methods: A prospective observational analysis was conducted on 850 patients presenting with suspected acute appendicitis. Radiological evaluation was performed in 93% of cases using ultrasound (n = 650) as the first-line modality, followed by computed tomography (n = 420) or magnetic resonance imaging (n = 120) in equivocal or high-risk cases. Imaging findings were correlated with operative and histopathological results. Diagnostic accuracy parameters and negative appendectomy rates were calculated. Results: Ultrasound demonstrated a sensitivity of 78% and specificity of 88%, with reduced accuracy in obese patients and operator-dependent variability. Computed tomography showed higher diagnostic performance with a sensitivity of 94% and specificity of 96%. Magnetic resonance imaging achieved sensitivity of 92% and specificity of 97%, particularly benefiting pregnant and younger patients. The negative appendectomy rate decreased from 18% with clinical assessment alone to 4.5% following systematic radiological evaluation. Conclusion: Radiological evaluation plays a pivotal role in the accurate diagnosis of acute appendicitis and significantly reduces negative appendectomy rates. A stepwise imaging approach, utilizing ultrasound followed by computed tomography or magnetic resonance imaging when indicated, enhances patient outcomes and supports evidence-based surgical decision-making...